Analysis of Visual Elements on Healthy Cendol 18 Product Packaging Design to Consumers - A M Ajie; D A W Sya’roni (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Analysis of Visual Elements on Healthy Cendol 18 Product Packaging. Nowadays, the visual elements in packaging design have started to develop. When it comes to the most important factors in food industry, packaging is one of it. For instance, in modern shopping the trend is that packaging always becomes an important factor. The target market for Healthy Cendol 18 is teenagers, since consuming junk food is not a new thing for them hence the production of this healthy and trendy product. This study aims to analyze the visual elements contained on Healthy Cendol 18 packaging design in order to provide results which are in accordance with the product’s target market. The method used is qualitative method. The data collection is conducted through Focus Group Discussion, literature study, packaging design analysis, as well as visual elements analysis. The researcher uses perception and packaging design theories. The conclusion is that packaging is indeed one of the most important factors for a product. It becomes some kind of a protector and media for the promotion of the product. The visual elements on Healthy Cendol 18 packaging design have their own characteristics and have been considered attractive for the customers. However, it is still necessary to improve them up to the point where they could be clearer and complete. Hopefully, this research could give an impact on the development of visual element design on any product’s packaging design by presenting a design which is in accordance with the product’s target market.